Can Illness Perceptions Predict Lower Heart Rate Variability following Acute Myocardial Infarction? - Princip, Mary; Scholz, Marco; Meister-Langraf, Rebecca E.; Barth, Jürgen; Schnyder, Ulrich; Znoj, Hansjörg; Schmid, Jean-Paul; Thayer, Julian F.; von Känel, Roland (Frontiers in Psychology, 2016)
Objective: Decreased heart rate variability (HRV) has been reported to be a predictor of mortality after myocardial infarction (MI). Patients’ beliefs and perceptions concerning their illness may play a role in decreased HRV. This study investigated if illness perceptions predict HRV at three months following acute MI. Methods: 130 patients referred to a tertiary cardiology centre, were examined within 48 hours and three months following acute MI. At admission, patients’ cognitive representations of their MI were assessed using the German version of the self-rated Brief Illness Perception Questionnaire (Brief IPQ). At admission and after three months (follow-up), frequency and time domain measures of HRV were obtained from 5-min electrocardiogram (ECG) recordings during stable supine resting. Results: Linear hierarchical regression showed that the Brief IPQ dimensions timeline (β coefficient = -0.29; p = .044), personal control (β = 0.47; p = .008) and illness understanding (β = 0.43; p = .014) were significant predictors of HRV, adjusted for age, gender, baseline HRV, diabetes, beta-blockers, left ventricular ejection fraction (LVEF), attendance of cardiac rehabilitation, and depressive symptoms. Conclusions: As patients’ negative perceptions of their illness are associated with lower HRV following acute MI, a brief illness perception questionnaire may help to identify patients who might benefit from a specific illness perceptions intervention.